advanced functions

Prove that

cscx / cosx = tanx + cotx

  1. 👍 0
  2. 👎 0
  3. 👁 691
  1. LS = cscx/cosx
    = (1/sinx)/cosx
    = 1/(sinxcosx)

    RS = sinx/cosx + cosx/sinx
    = (cos^2x + sin^2x)/(sinxcosx)
    = 1/(sinxcosx)
    = LS

    1. 👍 1
    2. 👎 0

Respond to this Question

First Name

Your Response

Similar Questions

  1. Pre-calculus

    Prove the following identities. 1. 1+cosx/1-cosx = secx + 1/secx -1 2. (tanx + cotx)^2=sec^2x csc^2x 3. cos(x+y) cos(x-y)= cos^2x - sin^2y

  2. Trig

    prove (cscx-secx/cscx+secx)=(cotx-1/cotx+1)

  3. Math

    1)A piano tuner uses a tuning fork. If middle C has a frequency of 264 vibrations per second, write an equation in the form d=sinw(t) for the simple harmonic motion. 2) Verify the identity tan^2X-cot^2X/tanX+cotX=tanX-cotX I'm not

  4. Pre calc

    Perform the indicated operation and simplify the result Tanx(cotx-cscx)

  1. Calculus

    Prove the identity cscx+cotx-1/cotx-cscx+1 = 1+cosx/sinx

  2. precalc

    tanx cotx ------- + ------- = 1 +secxcscx 1 - cotx 1- tanx prove the proof

  3. Trigonometry

    Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.

  4. trig

    (cotxsec2x - cotx)/ (sinxtanx + cosx) = sinx prove. i keep getting (if i start from the left side) = cosx instead of sinx please help!

  1. Math please help quick

    Which of the following are identities? Check all that apply. (Points : 2) sin2x = 1 - cos2x sin2x - cos2x = 1 tan2x = 1 + sec2x cot2x = csc2x - 1 Question 4. 4. Which of the following equations are identities? Check all that

  2. precal

    1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a

  3. Trigonometry

    Prove that tanx+cotx=2sec(2x) Thank you! :)

  4. a math

    Prove cotx-1/cotx+1 = sec2x - tan2x I prove till cotx-1/cotx+1 =1/1+tanx - tanx/1+tanx

You can view more similar questions or ask a new question.